Using the Ocean Health Index to Identify Opportunities and Challenges to Improving Southern Ocean Ecosystem Health - Longo, Catherine S.; Frazier, Melanie; Doney, Scott C.; Rheuban, Jennie E.; Humberstone, Jennifer Macy; Halpern, Benjamin S. (Frontiers in Marine Science, 2017)
The Antarctic coast and seas are considered some of the most pristine marine systems on Earth. Their comprehensive assessment is critical because meeting ambitious conservation objectives while maintaining sustainable human uses will be increasingly challenging with growing climate change impacts, recovery from past overharvesting, and potential revision of activities permitted with future revisions of the existing governance structure. We used the Ocean Health Index (OHI) to deliver an integrated assessment of the Antarctic marine ecosystems’ evolving ecological and social dimensions. The OHI provides a framework to evaluate sustainable delivery of benefits people want from healthy oceans by measuring progress towards 10 widely-held societal goals. These goals include, conservation objectives, as well as other objectives, so as to identify tradeoffs across multiple priorities. We adapted the Index to the unique aspects and data availability of Antarctica. OHI scores were calculated for each sub-region defined by the Convention for the Conservation of Antarctic Marine Living Resources (CCAMLR) as well as the region overall. OHI scores for conservation-related goals (biodiversity, clean water) were generally high, though with some stressor impacts (i.e., climate-driven decline of sea-ice, and pathogen pollution). However, a sensitivity test on the sea-ice habitat indicator showed biodiversity scores might be much lower in the vicinity of the Antarctic Peninsula. Preservation of lasting special places, captured in the sense of place sub-goal, scored relatively low due to limited extent of Marine Protected Areas in the Southern Ocean. In several cases, scores are low due to under-utilization of resources, rather than environmentally unsustainable practices (e.g., food provision, natural products, tourism and recreation). However, increased human activities would intensify the risk of pollution, pathogen contamination, and disturbance to wildlife, particularly if compounded with future climate change impacts. Therefore, scores may reflect the need to select more conservative targets for human use, articulated in international treaties, taking future risks into account. Our results highlight the need for more research on both natural and social science aspects of the Antarctic system, as well as the need to evaluate targets under different scenarios, so as to provide robust science-based advice for future decision-making in the region.